2019
DOI: 10.1093/cid/ciz129
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Low-level Viremia While on Antiretroviral Therapy Is an Independent Risk Factor for Virologic Failure

Abstract: Background Whether persistent low-level viremia (pLLV) predicts virologic failure (VF) is unclear. We used data from the US Military HIV Natural History Study (NHS), to examine the association of pLLV and VF. Methods NHS subjects who initiated combination antiretroviral therapy (ART) after 1996 were included if they had 2 or more VLs measured with a lower limit of detection of ≤50 copies/mL. VF was defined as a confirmed VL ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 31 publications
(45 reference statements)
7
58
1
2
Order By: Relevance
“…In this study, we observed LLV from 38.7% of participants, and this was much higher than the LLV occurrence (15-20%) in resource-rich settings with similar LLV definition criteria (50-1000 copies/ml) [18,37]. Multiple potential factors could explain these differences, including different ART regimens and frequency of testing [6]. However, because of the strict definition of VF used in this study, the occurrence of VF was substantially lower than previous reported data on both resource-rich regions [38,39] and resource-limited regions [2,7].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In this study, we observed LLV from 38.7% of participants, and this was much higher than the LLV occurrence (15-20%) in resource-rich settings with similar LLV definition criteria (50-1000 copies/ml) [18,37]. Multiple potential factors could explain these differences, including different ART regimens and frequency of testing [6]. However, because of the strict definition of VF used in this study, the occurrence of VF was substantially lower than previous reported data on both resource-rich regions [38,39] and resource-limited regions [2,7].…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, most previous studies have only evaluated the impact of different level LLV on VF, without considering the duration of LLV. A few studies found no significant association of low or medium levels LLV with varied duration [5,6,38]. However, the definition of VF in these studies was two consecutive viral loads of at least 500 copies/ml, which is rarely used in practice and differed from that used in this study.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…39 Similarly a persistent low-level viremia, defined as a VL of 50-199 copies/mL on at least 25% of measurements was associated with virological failure. 40 But clear cutoffs are lacking to allow identification of patients at high risk of virological failure. In our cohort, numerous patients experienced virological control soon after DNA GRT performance in the absence of any ART change.…”
Section: Discussionmentioning
confidence: 99%